2013
DOI: 10.1259/bjr.20130457
|View full text |Cite
|
Sign up to set email alerts
|

Which bowel preparation is best? Comparison of a high-fibre diet leaflet, daily microenema and no preparation in prostate cancer patients treated with radical radiotherapy to assess the effect on planned target volume shifts due to rectal distension

Abstract: The use of microenema is effective in reducing prostate shift and rectal CSA, consequently decreasing the incidence of geographical miss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 25 publications
(30 reference statements)
0
55
1
Order By: Relevance
“…Although institutional guidelines may vary, it is reasonable to instruct patients to strive for consistency with a comfortably full bladder, an empty rectum, and an antiflatulent diet for both simulation and treatment. Given the availability of online daily image guidance strategies for prostate EBRT, which minimize geographic misses of the prostate target volume, 96 preparation guidelines should not create excessive discomfort or inconvenience for patients 97 . Finally, the use of contrast (intravenous, intravesicular/ureteral, rectal) is generally not necessary for routine care.…”
Section: Techniques Of Patient Immobilization and Setupmentioning
confidence: 99%
“…Although institutional guidelines may vary, it is reasonable to instruct patients to strive for consistency with a comfortably full bladder, an empty rectum, and an antiflatulent diet for both simulation and treatment. Given the availability of online daily image guidance strategies for prostate EBRT, which minimize geographic misses of the prostate target volume, 96 preparation guidelines should not create excessive discomfort or inconvenience for patients 97 . Finally, the use of contrast (intravenous, intravesicular/ureteral, rectal) is generally not necessary for routine care.…”
Section: Techniques Of Patient Immobilization and Setupmentioning
confidence: 99%
“…28,29 This diversity may render it impossible for diet prescriptions or results from one center to be generalized to another. In addition, fermentation of foods by bowel flora ("microbiota") is a major source of gas in the large intestine and is highly variable between individuals and affected by 16 See Table 2 Yahya 17 See Table 3 Darud 19 See Table 2 Graf 23 See Table 3 CBCT, cone beam computed tomography; CT, computed tomography; PM, prostate motion; RC, rectal changes; RV, rectal volume.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the 18 studies employed more than 1 intervention limiting the conclusions that can be drawn from them 8,9,11,14,16,[19][20][21][22][23] (Table 1). Eleven studies reported significant results [8][9][10][11][12][15][16][17][18]20 (Tables 2-5). …”
Section: Rectal Emptying Strategiesmentioning
confidence: 99%
See 2 more Smart Citations